Kebijakan Hukum Pidana Dalam Upaya Penanggulangan Tindak Pidana Pencucian Uang Yang Dilakukan Oleh Korporasi - Randy Pradityo; Riri Tri Mayasari (Universitas Bengkulu, 2021)
Criminal law policy in the effort to combat crime has 2 (two) main means, namely penal and non-penal. The penal policy is formulated in the regulation to eradicate money laundering. In this provision, the corporation has the same responsibility as individuals (natuur person). Corporations that are suspected of committing the crime of money laundering must first be proven whether the act classified as money laundering was carried out by an individual or on behalf of the management or corporation so that it can be sanctioned according to their respective qualifications. Another problem is that the imposition of imprisonment in lieu of fines in this regulation does not include an explanation regarding the calculation of confiscated corporate assets as a reason for reducing imprisonment in lieu of fines. Therefore, the policy for formulating corporate responsibility should be made by taking into account the extent to which the corporation moves in money laundering crimes, taking into account the consequences of these crimes. In addition, the corporate responsibility formulation policy must comply with the general provisions in the Criminal Code as the main guideline.Keywords: Policy; Criminal Law; Money Laundering; Corporation; Kebijakan hukum pidana dalam upaya penanggulangan kejahatan memiliki 2 (dua) sarana utama, yakni penal dan non-penal. Kebijakan penal dirumuskan dalam regulasi pemberantasan tindak pidana pencucian uang. Didalam ketentuan tersebut, korporasi memiliki pertanggungjawaban yang sama dengan individu (natuur person). Korporasi yang diduga melakukan tindak pidana pencucian uang harus terlebih dahulu dibuktikan apakah perbuatan yang tergolong pencucian uang tersebut dilakukan oleh individu secara pribadi ataukah mengatasnamakan pengurus atau korporasi sehingga dapat dijatuhkan sanksi sesuai dengan kualifikasinya masing-masing. Problem lainnya adalah penjatuhan pidana kurungan pengganti denda dalam regulasi ini tidak mencantumkan penjelasan mengenai perhitungan kekayaan korporasi yang dirampas sebagai alasan pengurangan pidana kurungan pengganti denda. Maka dari itu, kebijakan perumusan pertanggungjawaban korporasi hendaknya dibuat dengan memperhatikan sejauh mana pergerakan korporasi dalam kejahatan pencucian uang, dengan mempertimbangkan akibat yang ditimbulkan dari kejahatan tersebut. Selain itu, kebijakan perumusan pertanggungjawaban korporasi haruslah berkesesuaian dengan ketentuan umum dalam KUHP sebagai pedoman utamanya.Kata Kunci: Kebijakan; Hukum Pidana; Pencucian Uang; Korporasi;